Optimized design and experiment of the three-arm transplanting mechanism for rice potted seedlings - Yin, Jianjun; Wang, Zeliang; Zhou, Maile; Wu, Luning; Zhang, Yan (International Journal of Agricultural and Biological Engineering, 2021)
The transplanting arm of two-arm transplanting mechanism is easy to cause seedlings injury and missing due to its faster speed relative to the seedlings. In order to solve the existed problems, a three-arm transplanting mechanism for rice potted seedlings was developed in this study. The developed three-arm transplanting mechanism for rice potted seedling can make the transplanting arm realize special trajectory and attitude through the unequal planetary gear transmission. The kinematic model of three-arm transplanting mechanism for rice potted seedling was established, and the optimal design software was developed. Based on the heuristic optimization algorithm named “parameter guide”, a set of satisfied mechanism parameters required by the rice potted seedling transplanting were obtained. The trajectory and attitude of three-arm transplanting mechanism used for the rice potted seedling were analyzed. Besides, the virtual simulation results were basically consistent with the optimization software results, and the correctness of theoretical analysis and virtual simulation were also verified by each other. When the developed transplanting mechanism picked up the seedling, the velocity of transplanting arm relative to the seedling was reduced by about 30%. The results showed that the injury rate of rice potted seedling transplanting mechanism was 0.04%, the missing rate of seedling was 1.4%, the integrity rate of seedling pot matrix was 96%, and the success rate of picking seedling was 99.92%.Keywords: agricultural machinery, transplanting mechanism, rice potted seedling, three-arm, optimal designDOI: 10.25165/j.ijabe.20211405.6844Citation: Yin J J, Wang Z L, Zhou M L, Wu L N, Zhang Y. Optimized design and experiment of the three-arm transplanting mechanism for rice potted seedlings. Int J Agric & Biol Eng, 2021; 14(5): 56–62.